Combined effects of acidic electrolyzed water and ultrasound treatments to decontaminate fresh tumeric - Santirote Keatsirirote (2020)
© Int. J. of GEOMATE. All rights reserved. The effect of electrolyzed oxidizing water (EO) and ultrasonic waves (US) on pathogenic control of fresh turmeric (Curcuma longa L.) were studied. Electrolyzed water was generated by electrolysis from 5% NaCl solution. The fresh turmeric samples were washed with EO at different concentrations (0, 100, 200, 300 and 400 mg/L residual chlorine). The percentage of reduction of total bacteria, yeast, mold and Escherichia coli was determined by compact dry plate. It was shown that EO at 300 mg/L significantly inhibited the cell growth. Then, the samples were washed with combination of EO and US for 10 minutes. It was shown that combination of EO and US significantly inhibited bacterial growth and EO 200 mg/L with US at 43 kHz had high value of log reduction when compared with other treatments. Therefore, combination of EO and US appeared to increasing pathogenic control of fresh turmeric.